PODCASTS AND STUDENT TEAMS ACHIEVEMENT DIVISIONS (STAD) TOWARDS EXTENSIVE LISTENING BY STUDENTS - Rajiha, Naila; Malihah, Noor; Muthmainnah, Nur (UIN Sumatera Utara, 2024)
Based on the preliminary experiment the students were perplexed by the English sounds, they struggled with motivation, and they hoped the benefit their peers. The research objectives were: (1) to determine the influence of podcast and STAD combination on the students’ extensive listening; and (2) to determine the significant difference between students' extensive listening before and after teaching using the combination of podcast and STAD. A Quantitative quasi experimental method was used. The research instrument was in form of objective test. The researchers gathered the documentation from the teacher's notes, the syllabus, lesson plan, and student development report. This quantitative data analysis uses SPSS for Windows. The findings of the study: (1) the combination of podcasts and STAD was more effective than three phase techniques collaborated with teacher’s reading aloud; and (2) In terms of enhancing extensive listening, there is a significant difference in achievement scores before and after the treatment. Some students were excited about improving their listening skills by using podcasts. They could grasp the native speaker comprehensively as well as maximize their role among students.